Bullying Intentions Among High School Students: Insights into Emotion Regulation and Cognitive Empathy - Sudirman Sudirman; Abdul Rahim Karim; Muhammad Irfan Hasanuddin (Jurnal Pendidikan Progresif, 2026)
Bullying has emerged as a serious public mental health crisis in Indonesian educational settings, affecting adolescents' psychosocial well-being at multiple levels. Despite rising case numbers reported by national institutions, most school-based interventions remain reactive and punitive, failing to address the underlying psychological mechanisms that precede bullying behavior. Ajzen's Theory of Planned Behavior (TPB) offers a useful frame here. Emotion regulation and cognitive empathy have been theoretically and empirically linked to aggressive intentions. However, their roles have rarely been examined through in-depth qualitative inquiry, particularly in the Indonesian context. This study aimed to explore how emotion regulation and cognitive empathy shape bullying intentions among senior high school students in Palopo City, and to identify key themes underlying their interplay within real school contexts. A qualitative multiple-case study design was employed, involving 24 purposively selected participants from State High School 1 and State High School 3 in Palopo City, comprising students, school counselors, and homeroom teachers. Data were gathered through in-depth interviews, participatory observation, and document analysis, then analyzed using Braun and Clarke's thematic analysis framework. Trustworthiness was established through source triangulation and member checking. Five core themes emerged; (1) emotion dysregulation, particularly failures in cognitive reappraisal, as a primary trigger of bullying intentions; (2) cognitive empathy deficits, especially low perspective taking, enabling moral disengagement; (3) peer group pressure accelerating bullying norms; (4) a substantial teacher-student perception gap undermining intervention effectiveness; and (5) maladaptive coping strategies sustaining cycles of aggression. Bullying intentions among adolescents are deeply rooted in deficits of emotion regulation and cognitive empathy, amplified by collectivist peer dynamics. Schools need to shift from punitive responses toward proactive social-emotional learning programs that explicitly cultivate cognitive reappraisal and perspective-taking skills as core psychological competencies. Keywords: bullying intention, cognitive empathy, emotion regulation, preventive strategy, qualitative case study.